2018
DOI: 10.2147/dddt.s148970
|View full text |Cite
|
Sign up to set email alerts
|

Burden of heart failure on caregivers in China: results from a cross-sectional survey

Abstract: PurposeFamily and friends play a pivotal role in caring for patients with heart failure (HF); however, evidence of the impact of caregiving is limited. The objectives of this study were to describe the burden of caregiving on informal caregivers of patients with chronic HF in China.Materials and methodsA cross-sectional survey of cardiologists, their patients with HF, and those patients’ caregivers was conducted. Patient record forms were completed by 150 cardiologists for 10 consecutive patients. Caregivers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 23 publications
(40 reference statements)
3
29
0
2
Order By: Relevance
“…As a result, they may have less time for friends and other family members. When assessing the impact of care on lifestyle, 33% of caregivers reported a significant reduction in social activity, and as many as 74% said that patient care had led to changes in their own plans or complete planning avoidance [30]. This is consistent with the studies of Negarandeh et al, in which 53% of the caregivers of HF patients were reported to suffer from social isolation.…”
Section: The Burden Of Caregivers Of Patients With Heart Failuresupporting
confidence: 79%
See 2 more Smart Citations
“…As a result, they may have less time for friends and other family members. When assessing the impact of care on lifestyle, 33% of caregivers reported a significant reduction in social activity, and as many as 74% said that patient care had led to changes in their own plans or complete planning avoidance [30]. This is consistent with the studies of Negarandeh et al, in which 53% of the caregivers of HF patients were reported to suffer from social isolation.…”
Section: The Burden Of Caregivers Of Patients With Heart Failuresupporting
confidence: 79%
“…The most frequent ailments included: stress, prolonged fatigue, lack of energy, sleep problems, migraines, and depression. It is all the more worrying that the majority of those who care for are older people, who feel the consequences of physical exhaustion much faster [30][31][32]. The deterioration of their health was related in particular to variables such as advanced age of the patient, a greater number of comorbidities, and worse functioning of the patient [33].…”
Section: The Burden Of Caregivers Of Patients With Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“… 30 , 31 Finally, the EQ-5D-3L has just 1 question that assesses the emotional well-being of patients (“I am not/moderately/extremely anxious or depressed”), so this element of HRQoL may be under-represented. 15 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…PSCs were completed by the same patients, and caregiver self-completion questionnaires were completed by the informal caregivers of the patients (results gathered from the caregiver self-completion questionnaires have been reported by Jackson et al). 15 The questionnaires were developed empirically, and their pharmacometric properties were not systematically assessed. The questionnaires were developed with input from experts in HF care; the concepts deemed most relevant to patients were selected empirically, and not as result of a formal process defining a conceptual framework, endpoint model and content validity, usually required to validate a patient-reported outcome measure (Ref FDA Guidance for Industry.…”
Section: Methodsmentioning
confidence: 99%